Bacterial etiologies, antimicrobial susceptibility profiles and associated factors among patients with otitis media referred to Nekemte Public Health Research and Referral Laboratory Center, Western Ethiopia: A cross-sectional study - Endalu Tesfaye Guteta; Fedasan Alemu Abdi; Seifu Gizaw Feyisa; Betrearon Sileshi Kinfu; Tadese Bekele Tafesse (BMC Microbiology)
Abstract Background Otitis media is among the leading causes of illnesses responsible for causing hearing problems and adding significant costs to the public health system. Bacteria are the most common causative agents for otitis media. Currently, there is little information on the prevalence and antimicrobial susceptibility patterns of pathogenic bacterial isolates from patients with otitis media in Ethiopia. Methodology A laboratory – based cross-sectional study was conducted from June to September 2023 among 242 patients with otitis media referred to Nekemte Public Health Research and Referral Laboratory Center. Sociodemographic and clinical data were obtained by trained nurses and/or health officers in face-to-face interviews using structured questionnaires. Middle ear discharge samples were collected by Ear, Nose and Throat (ENT) specialists (Otolaryngologist) following all aseptic techniques. Conventional culture, different biochemical tests and antimicrobial susceptibility testing were performed for all the isolated bacteria. Reference strains were used as a positive and negative controls. The data were checked for completeness and consistency, entered into EpiData version 4.6.06 and analyzed by SPSS version 25. Logistic regression analysis was performed to determine the associated factors of otitis media. Adjusted odds ratio was used to determine strength of association. Statistical significance was obtained at p-value of below 0.05. The data were interpreted using graphs, tables, and results statements. Results A total of 242 middle ear discharge samples were collected and cultured from which 212 (87.6%) were culture positive. A total of 228 pathogenic bacterial isolates were recovered. The predominant bacterial isolates were S. aureus 92 (40.4%) followed by P. aeruginosa 33 (14.5%) and E. coli 24 (10.5%). One hundred and fifty-one (66.2%) bacterial pathogens were multidrug resistant. Piperacillin-tazobactam and tobramycin were relatively common drugs to which most of the isolates were susceptible while they were most resistant to ampicillin and tetracycline. Purulent discharge (p-value = 0.001), middle ear discharge ≥ 14 days (P-value = 0.000) and a history of active/passive smoking (P-value = 0.043) were significantly associated with otitis media. Conclusion The prevalence of bacterial pathogens, most of which were multidrug-resistant, was high among patients with otitis media. A significant association was observed with purulent ear discharge, chronic otitis media, and passive or active smoking. Choosing the proper antibiotic for the treatment of bacterial infection is crucial.